Gender in South Africa - Kirkwood, Daniel (World Bank, Washington, DC, 2018)
Despite strong representation in national politics and their higher levels of enrollment in secondary and higher education, South African women face numerous constraints that prevent them from fully contributing to poverty reduction and shared prosperity. Many of these constraints are underpinned by social norms that cause women to: have less time for productive activities; avoid science, technology, engineering, and mathematics (STEM) subjects in their formal education; enter lower paid jobs and sectors; accept the use of violence (including by their male spouses and partners); have less access to productive assets. These norms, while seen across many countries around the world, were not formed in a vacuum. Thus, it is important to recognize the role that specific factors in the history of South Africa have played in the development and entrenchment of certain social norms and practices. The legacy of exclusion emanating from colonialism and apartheid disrupted family structures, aiding transactional sex and the spread of human immunodeficiency virus and acquired immunodeficiency syndrome (HIV and AIDS), and leaving children vulnerable to abuse and without male role models. Similarly, apartheid was characterized by the creation of a large low skilled population, and the legacy of this can still be seen with poorer access to health, education, and economic opportunities among the African and colored population. Evidence suggests that the frustrations that young men feel as a result of not being able to meet commonly held expectations of manhood (such as providing for a family) may result in high rates of crime and gender-based violence. This note reviews available research on gender in South Africa for the South Africa systematic country diagnostic.